Effect of Interest Rate Subsidies on Firm Performance and Investment Behavior during Economic Recession: Evidence from Vietnam1. Issue 2 (5th June 2013) - Dinh, Tuan‐Minh; Malesky, Edmund; To, Trung‐Thanh; Nguyen, Duc‐Thanh
<x xml:space="preserve">Abstract</x> This paper aims to quantitatively evaluate the microeconomic consequences of the 4‐percent interest rate subsidy program, the main component of the Vietnamese Government's economic stimulus package in 2009, which was intended to assist recovery from the global economic and financial recession. Our analyses based on the Provincial Competitive Index 2009 survey and accounting data of firms listed on Vietnam's two stock exchanges show that firms that received subsidized loans were more likely to increase labor, to expand investment and to possess optimistic business plans. However, we find evidence that not all business activity generated by the stimulus led to productivity increases: a non‐trivial proportion of subsidized loans were not used to invest in production or expansion, but for speculative activities such as real estate and stock market trading.